Genetic diversity and relationships of broomcorn millet based on trnT-trnL and GBSSI sequences - Xiaohan Yu; Funa Tan; Xiaoxing Wang; Jiandong Ren; Shaoxiong Liu; Yue Wang; Xuxia Xin; Ruonan Wang; Yingxing Zhang; Zhaoyan Chen; Jishan Xiang; Minxuan Liu (PLoS ONE, 2025)
Broomcorn millet (Panicum miliaceum L.) is the oldest crop originating in China. The routes of transmission have been the focus of broomcorn millet research. This study evaluated genetic diversity and relationship of 430 broomcorn millet accessions (369 domestic accessions from nine regions and 61 foreign accessions from twenty-four counties) based on the chloroplast DNA trnT-trnL spacer sequence and nuclear DNA GBSSI sequence to explore the domestication of broomcorn millet. The trnT-trnL sequence was highly conserved, while the diversity of GBSSI sequence was significantly higher. Results of this study suggest that broomcorn millet may have originated from the core area (including Shanxi, Shaanxi, Inner Mongolia, Ningxia and Gansu) and then spread westward to Xinjiang and into Eurasia, or eastward from Shanxi to Hebei, Inner Mongolia and northeast China. Xinjiang is crucial for broomcorn millet to spread westward. This study revealed the genetic diversity of broomcorn millet accessions from different geographical sources, laying a theoretical foundation for further analysis of the evolutionary origin of this taxon.